Facile fabrication of a vanadium nitride/carbon fiber composite for half/full sodium-ion and potassium-ion batteries with long-term cycling performance. Issue 19 (6th May 2020) - Xu, Lihong; Xiong, Peixun; Zeng, Lingxing; Liu, Renpin; Liu, Junbin; Luo, Fenqiang; Li, Xinye; Chen, Qinghua; Wei, Mingdeng; Qian, Qingrong
Abstract : A VN/CNF composite was fabricated as an anode material exhibiting superior performance for half/full sodium-ion and potassium-ion batteries. Abstract : Vanadium-based composite anodes have been designed for applications in alkali metal ion batteries, including lithium-ion batteries (LIBs), sodium-ion batteries (SIBs) and potassium-ion batteries (PIBs). However, the problems of inferior long-term cycling stability caused by the large volume change and dissolution of vanadium-based active materials during cycles and slow diffusion for large radii of Na + and K + still limit their underlying capability and need to be addressed. In the present work, we initially designed and fabricated a vanadium nitride/carbon fiber (VN/CNF) composite via a facile electrospinning method followed by the ammonization process. The obtained VN/CNF composite anode exhibited excellent half/full sodium and potassium storage performance. When used as an anode material for SIBs, it delivered a high capacity of 403 mA h g −1 at 0.1 A g −1 after 100 cycles and as large as 237 mA h g −1 at 2 A g −1 even after 4000 cycles with negligible capacity fading. More importantly, the VN/CNFs//Na3 V2 (PO4 )3 full cell by coupling the VN/CNF composite anode with the Na3 V2 (PO4 )3 (NVP) cathode also exhibited a desirable capacity of 257 mA h g −1 at 500 mA g −1 after 50 cycles. Besides, when further evaluated as an anode for PIBs, the VN/CNF composite anode achieved a large capacity of 266 mA h g −1 after 200 cycles at 0.1 A g −1 and maintained a stable capacity of 152 mA h g −1 at 1 A g −1 even after 1000 cycles, showing significant long-term cycling stability. This is one of the best performances of vanadium-based anode materials for SIBs and PIBs reported so far.